Effect of incremental intensities on the spinal morphology and core muscle activation in competitive cyclists - Muyor, J. M.; Antequera-Vique, J. A.; Oliva-Lozano, J. M.; Arrabal-Campos, F. M. (Sports Biomechanics, 2023)
Cycling is a sport where cyclists predominantly adopt a sitting posture, with the trunk tilted forward. This posture requires a high volume of training and duration in several intensities of effort. This study aims to: 1) evaluate the behaviour of the thoracic and lumbar spine flexion and sacral inclination in the sagittal plane, the thoracic and lumbar spine flexion in the frontal plane, and the trunk torsion in the transverse plane; 2) compare the activation of the core muscles as the intensity of effort increases during an incremental test in cycling, and 3) identify which core muscle has a greater activation in each intensity zone. The spinal posture and the activation of the eight core muscles were evaluated in twelve competitive cyclists during incremental cycling intensities. Thoracic and lumbar spine flexion and sacral inclination statistically increased as the intensity of effort increased (Start < VT1 < VT2 < VO2max). A significant increase in muscle activation was observed in all core muscles evaluated as the intensity increased. The rectus abdominis showed statistically significant greater muscle activation than the other core muscles evaluated. In conclusion, as the intensity of effort in cycling increases, cyclists significantly increase the thoracic and lumbar spine flexion, the sacral inclination in the sagittal plane, the thoracic and lumbar spine flexion in the frontal plane, trunk rotation in the transverse plane, as well as the activation of the core muscles.